Coastal Fish Research - Tiralongo, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a collection of a series of articles on several aspects of coastal fish biology and ecology. Coastal fish are key components of marine ecosystems, and the aim of this book is to present relevant research on these wonderful animals and to provide insights for future research in this field.